2022
DOI: 10.1001/jamahealthforum.2022.1229
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cancer-Related Spending and Mortality Rates in the US vs 21 High-Income Countries

Abstract: IMPORTANCE Studies using data from before 2011 concluded that the cost of US cancer care is justified given improved outcomes compared with European countries. However, it is unclear whether contemporary US cancer care provides better value than that of other high-income countries.OBJECTIVE To assess whether cancer mortality rates in 2020 were lower in countries with higher cancer-related spending, and to estimate across countries the incremental cost per averted cancer death. DESIGN, SETTING, AND PARTICIPANTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…Cross-sectional studies confirm that large health care expenditures are associated with lower cancer mortality. However, studies of the periods up to and after 2011 in the United States have shown that this is not a linear relationship [ 13 ]. The group with the highest investment in both financial and human resources ranked second, in terms of breast cancer mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies confirm that large health care expenditures are associated with lower cancer mortality. However, studies of the periods up to and after 2011 in the United States have shown that this is not a linear relationship [ 13 ]. The group with the highest investment in both financial and human resources ranked second, in terms of breast cancer mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…While the initiation of a nationwide screening program may have a primary role in lowering colorectal cancer ASMR through early detection and treatment of cancerous lesions in their earlier state, there are additional policy-induced contributing factors to the decrease in ASMR over the years including increasing awareness for higher adherence rates of screening [ 3 , 15 ], better treatment options available through insurance coverage [ 16 ], and nationwide quality assessment of the treatment given to colorectal cancer patients [ 17 ]. This has in turn led to a higher standard of care where Korea is now one of the leading countries in terms of colorectal cancer treatment and survival rates [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…During 2022, more than 1000 manuscripts were submitted to JAMA Health Forum from authors in 30 countries across 6 continents, including more than 700 research manuscripts and nearly 300 opinion manuscripts (Table). New submissions rose from about 600 research manuscripts and 250 opinion manuscripts in 2021, representing increases of 21% and 14%, respectively.…”
mentioning
confidence: 99%